1992
DOI: 10.1098/rsta.1992.0012
|View full text |Cite
|
Sign up to set email alerts
|

Flame stretch rate as a determinant of turbulent burning velocity

Abstract: A rational basis for correlating turbulent burning velocities is shown to involve the product of the Karlovitz stretch factor and the Lewis number. A generalized expression is derived to show how flame stretch is related to the velocity field. A new dimensionless correlation of experimental values of turbulent burning velocities is presented. Dimensionless groups also are used in correlations of laminar and turbulent flame extinction stretch rates. A distribution function of stretch rates in turbulent flames, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(59 citation statements)
references
References 62 publications
0
54
0
1
Order By: Relevance
“…Further examinations on flame extinction were conducted by Bradley et al [31]. The authors showed that KaLe > 1.5 corresponded to the lower boundary of the quenching process and a new quench limit was established to be KaLe ≥ 6 [31]. This therefore shows that turbulent flame quenching would not take place in multi-obstacle explosions unless the turbulence levels were high enough to achieve close to detonation conditions.…”
Section: Turbulent Burning Velocity As a Function Of The Predicted Pementioning
confidence: 99%
See 2 more Smart Citations
“…Further examinations on flame extinction were conducted by Bradley et al [31]. The authors showed that KaLe > 1.5 corresponded to the lower boundary of the quenching process and a new quench limit was established to be KaLe ≥ 6 [31]. This therefore shows that turbulent flame quenching would not take place in multi-obstacle explosions unless the turbulence levels were high enough to achieve close to detonation conditions.…”
Section: Turbulent Burning Velocity As a Function Of The Predicted Pementioning
confidence: 99%
“…Abdel-Gayed et al [30] presented another correlation of flame quenching for Ka ≥ 1. Further examinations on flame extinction were conducted by Bradley et al [31]. The authors showed that KaLe > 1.5 corresponded to the lower boundary of the quenching process and a new quench limit was established to be KaLe ≥ 6 [31].…”
Section: Turbulent Burning Velocity As a Function Of The Predicted Pementioning
confidence: 99%
See 1 more Smart Citation
“…Early generalisations of measured values of u t /u l were expressed first in terms of the product of Karlovitz and Lewis number of the deficient reactant, KLe [3], then later, KMa sr [6,13]. Latterly, it has proved necessary to separate K and Ma sr [17][18][19].…”
Section: Probability Of Burning and The Turbulent Burning Velocitymentioning
confidence: 99%
“…Asymptotic analysis attributed the changes to thermo-diffusive effects and possible flame extinctions at high flame stretch rates. The influence of the latter also featured in quantifications of a probability of burning, P b [2,3].…”
Section: Introductionmentioning
confidence: 99%